(3GdMSf GdUQjM aj eGFI edjMs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Ydi eG hgH aEfj hbYJ bOjeG Ydi eG LeYg GdCaGVd TcQ Gddg SYjge (B- (3aj ChUGa GdZdeGf, cGdKYGdHj hZjQg adeG JQhb dj aj GhQGb ef Pdc RaQI hdG CeGdJ YWaj efgG cCS NeQI s
(3BNQgG (B:s
(3heTGZdj bdJ deG HOG jQhb aj GdbdH haj GdYjf s
(3GfXQ GdLRA GdChd HQbe (B195 (3COHs
(3hgh aj cTa GdXfhf(B: (3MSf GdJUQjMs
(3hQO CjVkG JMJ Qbe (B2202s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs